Avaliação de linhagens mutantes de Trichoderma harzianum na indução de resistência ao mofo branco e promoção do crescimento de feijoeiro comum (Phaseolus vulgaris) - Brandão, Renata Silva (2019)
The common bean (Phaseolus vulgaris L.) is the most cultivated species among the other species of the Phaseolus genus with 95% of world production. There are several pathogens of epidemiological importance that cause economic damage to this crop, among which, Sclerotinia sclerotiorum, Which causes white mold. This pathogen can survive in seeds for more than three years and, through them, establish the disease in new areas. The fungus Trichoderma spp. stands out as an important biological control agent for S. sclerotiorum. Trichoderma mutants may be an alternative not only for biological control, suggesting that strains that overexpress aquoporins help the bioagent survive by providing protection against osmotic shock and ΔEpl-1 mutant, on the other hand, is involved in the process of mycoparasitism against phytopathogenic fungi, with responses in the protection of plants not yet defined. The aim of the study was to evaluate the physiological and biochemical aspects regarding the use of the fungus Trichoderma mutants Aquo and ΔEpl-1 in common bean plants against S. sclerotiorum. The experiment was conducted at Embrapa rice and beans and at the UFG Enzymology Laboratory. Physiological and biochemical analyzes were carried out on leaves and roots of common bean plants, produced from seeds treated with the wild isolate All 42 of Trichoderma harzianum, their strains of mutants Aquo and ΔEpl-1, and control without treatments. The Aquo treatment promoted an increase of 25% in the leaf area of the plants in relation to the control (p <0.05) and surpassed the treatments All42 and ΔEpl-1 by 28% and 91%, respectively. The specific activity of the enzyme β-1,3 glucanase was higher in plants treated with T. harzianum ΔEpl-1, in leaves and roots with 2.07 Umg-¹ and 2.57 Umg-¹, with and without inoculation of S. sclerotiorum presented 2.27 Umg-¹ and 2.34 Umg-¹, respectively, presenting a significant result on the leaf in relation to the other treatments.